The Impact of environmental orientation and Sustainability Innovation on Sustainable Consumer Behavior: The Role of Education as Mediator - Mehmood, Sultan Tahir; Tahir, Naila; Kiani, Sidra; Hammad, Mohammad; Tahir, Raza Tahir; Hamid, Ali Raza (Archives of Business Research, 2019)
The present research has been conducted to assess the mediating role that education through different modes could play in formulating sustainable consumer behavior. Moreover, the impact of environmental orientation on sustainability innovation has also been assessed. A non-probability judgmental survey approach has been used in the study. This way of sampling intended to include 161 respondents in total as a focus group where all the respondents are professionals either from business firms or from educational institutions. The research instrument in this study has been pretested and developed by the researcher based on an interview guide for unstructured interviews that elicited first-hand information; the information obtained has been linked with concurrent researches. The study has revealed that environmental orientation and sustainability as innovation can lead to a sustainable consumer behavior. Moreover, all different modes of education play a role of mediation between sustainability innovation and sustainable behavior but no mediation has been reported between environmental orientation and sustainable behavior.